Composing rock 'n' roll stories from the usage data blues - Brooks-Kieffer, Jamene (My University, 2009)
Don't sing the blues about your usage data. Learn how to make it rock! We will review intermediate Excel tools for handling and consolidating data. Then we will derive meaning from consolidated data and communicate it to stakeholders in stories that are as accessible as a rock 'n roll song.
Keywords: Usage data; Excel; SFX; Stories